Studies of maize streak virus isolates from grass and cereal hosts in Nigeria - Mesfin, T.; Bosque Pérez, N.A.; Buddenhagen, I.W.; Thottappilly, G.; Oloyede, S.O. (Scientific Societies, 1992)
Maize streak geminivirus (MSV) isolates originating from maize, other cerealsand 18 grass species in Nigeria were characterized based on symptoms, transmission, host range and serological tests. All isolates could be transmitted to MSV-susceptible sweet corn cv. Golden Bantam using Cicadulina storeyi as a vector, but only some could be transmitted to MSV-susceptible maize cv. Pool 16. Differences were observed among isolates in symptom severity (ranging from very mild to severe), av. time of symptom appearance, percentage transmission to maize and host range. Of the 24 isolates tested, 18 reacted with an antiserum to a severe MSV maize isolate from Nigeria, 4 each with antisera to Panicum maximum and sugarcane isolates, and none with digitaria streak geminivirus antiserum. It is suggested that streak found in many grasses in Nigeria is not readily transmissible to susceptible field maize and that some of the weeds most likely to be involved in perpetuating an epidemiologically competent maize strain of MSV are Axonopus compressus, Brachiaria lata and Setaria barbata.